Exergy and Exergoeconomic Analysis of a Combined Cooling, Heating, and Power System Based on Solar Thermal Biomass Gasification - Jin Wu (Energies, 2019)
The purpose of this paper is to improve the utilization of renewable energy by exergy and exergoeconomic analysis of the novel combined cooling, heating, and power (CCHP) system, which is based on solar thermal biomass gasification. The source of heat to assist biomass and steam gasification is the solar heat collected by a dish collector, and the product gas being fuel that drives the internal combustion engine to generate electricity and then to produce chilled/hot water by a waste heat unitization system. The analysis and calculation of the exergy loss and exergy efficiency of each component reveal the irreversibility in the heating and cooling conditions. Then, the exergoeconomic costs of multi-products such as electricity, chilled water, heating water, and domestic hot water are calculated by using the cost allocation method based on energy level. The influencing factors of the unit exergy cost of products are evaluated by sensitivity analysis, such as initial investment cost, biomass cost, service life, interest rate, and operating time coefficient. The results reveal that the internal combustion engine takes up 49.2% of the total exergy loss, and the most effective method of products cost allocation is the exergoeconomic method based on energy level and conforms to the principle of high energy level with high cost.